ANALISIS KEBUTUHAN ALAT ANGKUT TBS DI PT. BERAU KARETINDO LESTARI KECAMATAN SEGAH KABUPATEN BERAU PROVINSI KALIMANTAN TIMUR - Ambrosius Edison; Humairo Aziza; Wartomo (JURNAL AGRIMENT, 2021)
This research is motivated by the processing of palm oil, transportation factors get special attention.The transportation of palm fruit from the garden to the factory should be as fast as possible so that thefruit harvested today can be processed directly so that free fatty acids are not high. Extensive oil palmplantations and garden conditions far from the factory, it will be more difficult to regulate the entry ofFresh Fruit Bunches (TBS) to the Palm Oil Factory (PKS), so that the company must have a goodmanagement system that can run effectively and efficiently so that it needs proper transportation forperushan so that it can transport all tbs harvested by minimizing time, cost and maintain the quality ofTBS.From the description above, the formula that can be formulated in this study is to know the time oftransportation, the needs of transport equipment and what obstacles are encountered at the time of TBStransportation. While the limitations of the problem there is tbs transport research contained in fadelingBrafo, Alfah and Delta with different distances (near, medium and farthest). The purpose of this researchis to know the process of planning the needs of TBS conveyances, as well as knowing the obstacleswhen transporting TBS.The results of research conducted at PT. Berau Karetindo Lestari shows that tbs transportationplanning includes the production of TBS per day, TBS transport time, availability of conveyance,transportation needs and constraints in transportation. In Bravo afdeling requires 2 units of tarktor, forafdeling Alfah 4 units taktor, and afdeling Delta requires 3 units of tractor. As for the needs of the truckon Loading ramp 1 as many as 10 units and Loading ramp 2 to 8 units. This is obtained after calculatingthe number of transport equipment needs to transport TBS every day. For the overall needs of thecompany, tractors are needed as many as 17 and DT as many as 18 units. As for the obstacles at thetime of tbs transportation, namely, the road conditions in TPH are not good and the distance of thefactory is so far that it takes so much time to get to the factory.